PEMBANGUNAN GAME AYO TARIK BERBASIS ANDROID - Masda Rahadian; Suzan Agustri; Nazori Suhandi (UNIVERSITAS INDO GLOBAL MANDIRI)
Multimedia applications develops very rapidly, particularly in the smartphone sector. The use of smartphone now is not only used as a medium of communication course. Smartphone later used as a means of entertainment, one of which is to play games. The game has become one of appendages application in a smartphone, one of them based on android smartphone. Mobile games is a game that is designed and played by mobile devices, as PDA (Personal Digital Assistant), smartphone, tablet PC (Personal Computer), and portable media player. Their mobile advantage play games is portability, the players can play games wherever they want for they have mobile devices which are able to run mobile games. As one traditional games, pull mine has become a sport that are very popular in indonesia. As other traditional game, game pull mine is very known by almost all Indonesians and often contested besides on the commemoration of indonesia independence in august, this game is often performed on anniversary of the city so district or even in celebration of the large religion. Android has become an operating system mobile favorite users because ease still and many features that can be used to apply the game will be made. Metode the development of this game adopt methodology multimedia development or MDLC (Multimedia Development Life Cycle). But to achieve this is needed an application programming that could support the game, will use Adobe Flash CS6. Testing the system with black box and testing beta. The results of the tryouts system shows that application program that have been made considered able to categorized either as alternative media entertainment